HUBUNGAN PERHATIAN ORANG TUA DENGAN HASIL BELAJAR GAMBAR KONSTRUKSI BANGUNAN SISWA KELAS XI TGB SMK NEGERI 1 TANJUNG RAYA - 2124-2127, M. Dimas Dermawan (CIVED, 2018)
Abstract— This research was conducted in SMK Negeri 1 Tanjung Raya and backed by the number of students who scored below 75 on the subject of Construction Building Drawing. The low learning outcome is caused by many factors such as the lack of attention of parents to the students. This study aims to reveal the relationship between the attention of parents with learning outcomes Student class XI TGB SMK Negeri 1 Tanjung Raya. This type of research is a descriptive study in the form of correlation with the total population of 30 people and the sample test using total sampling technique. Data analysis techniques used are: 1) Descriptive analysis, 2) Test requirements analysis, consisting of normality test and linearity test to prove that the distribution of data derived from samples of normal and linear distributed, and 3) Hypothesis Testing. The results of this study can be concluded that there is a sufficient and significant relationship between the attention of parents with the learning results of Building Construction Building students of class XI TGB SMK Negeri 1 Tanjung Raya. This can be seen from the correlation coefficient price of 0.468, is in the category of a sufficient relationship (located between 0.40 - 0.70). Keywords: Parents' Concern, Learning Outcomes, Building Construction Drawings